2007
DOI: 10.1016/j.cub.2007.04.034
|View full text |Cite
|
Sign up to set email alerts
|

ANR5, an FGF Target Gene Product, Regulates Gastrulation in Xenopus

Abstract: Gastrulation is a morphogenetic process in which tightly coordinated cell and tissue movements establish the three germ layers (ectoderm, mesoderm, and endoderm) to define the anterior-to-posterior embryonic organization [1]. To elicit this movement, cells modulate membrane protrusions and undergo dynamic cell interactions. Here we report that ankyrin repeats domain protein 5 (xANR5), a novel FGF target gene product, regulates cell-protrusion formation and tissue separation, a process that develops the boundar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 26 publications
1
32
0
Order By: Relevance
“…As a result, Dsh and PKC␦ are not localized to the plasma membrane and RhoA is not activated. Recently, it was reported that Xenopus ANR5 protein, which can modulate gastrulation movements, interacts with xPAPC, corroborating the role of PAPC in intracellular signaling (Chung et al 2007). Our results presented here show that gastrulation movements can be modulated by sequestration of the inhibitor Spry by the cytoplasmic domain of xPAPC.…”
Section: Sion Of Xpapc (Uas-papc) M-papc (Uas-m-papc) or Xaxpc (Uassupporting
confidence: 89%
“…As a result, Dsh and PKC␦ are not localized to the plasma membrane and RhoA is not activated. Recently, it was reported that Xenopus ANR5 protein, which can modulate gastrulation movements, interacts with xPAPC, corroborating the role of PAPC in intracellular signaling (Chung et al 2007). Our results presented here show that gastrulation movements can be modulated by sequestration of the inhibitor Spry by the cytoplasmic domain of xPAPC.…”
Section: Sion Of Xpapc (Uas-papc) M-papc (Uas-m-papc) or Xaxpc (Uassupporting
confidence: 89%
“…Examples of this include the overexpression of Xsprouty2, a negative regulator of Fgf signaling (Nutt et al, 2001), and the knockdowns of neurotrophin receptor homolog (NRH) and ankyrin repeat domain protein 5 (Anr5), both Fgf downstream targets (Chung et al, 2005;Chung et al, 2007), which result in the inhibition of cell movement during convergent extension. In addition, chimeric analyses of the Fgfr1-knockout mouse have shown that these mutant cells fail to move away from the primitive streak (Ciruna and Rossant, 2001;Ciruna et al, 1997).…”
Section: Research Articlementioning
confidence: 99%
“…It has been shown that PAPC is involved in convergence and extension movements during gastrulation via two independent pathways, i.e., the Frizzled-7 PCP signaling pathway and Ccadherin-mediated adhesion (53,167,369,380). In addition, ankyrin repeats-domain protein-5 (ANR5) binds to the cytoplasmic domain of PAPC and regulates gastrulation (58). Moreover, PAPC forms a complex with FLRT3 and C-cadherin, and PAPC controls C-cadherin-mediated adhesion by regulating FRT3 activity via GTPase RND1 (54).…”
Section: Protocadherin 8 (Arcadlin) and Paraxial Protocadherinmentioning
confidence: 99%